New Chair Alliance - Katherine Frank; Daniel Wheeler (Academic Chairpersons Conference Proceedings, 2016)
Transition to new roles and responsibilities Satisfactions from being a chair – what makes a difference Scoping out the work for the whole year Managing the everyday Planning for the future Your development
Keywords: New Chair Alliance